Intellectual capital measurement in higher education institutions context from the professors perspective - Vargas-Atencio, Yuranis (2024)
Intellectual capital has aroused growing interest in higher education; however, one area for improvement in its study is how to measure it adequately. Therefore, it is necessary to have instruments based on current models of intellectual capital. This study aims to design and validate an intellectual capital measurement scale in accredited higher education institutions (HEIs) from the perspective of professors. The study was instrumental because a measurement scale was developed. The sample consisted of 341 professors from six accredited HEIs on the Colombian Caribbean Coast. The statistical analysis consisted of three stages: item analysis, collection of validity evidence based on the internal structure and the relationship with other variables, and reliability analysis using the internal consistency method. The scale's internal structure corroborated intellectual capital composition based on human, structural, and relational components. Regarding convergent evidence, all variables possess this source of validity evidence. Reliability levels were also good. Previously, an instrument has yet to be developed those measures intellectual capital in HEIs from the perspective of professors. This study provides a scale that focuses on the characteristics of this stakeholder and is based on an innovative model of intellectual capital composed of human, structural, and relational capital. The theoretical contribution of the study lies in developing a test based on two current models of intellectual capital: the Intellectus model and the Balanced Scorecard model. It also contributes to practice by providing a tool for measuring intellectual capital that allows its adequate management, improvement, and decision-making within higher education.